An investigation of private employment agency fees performance: a case of Ministry of Public Service Labour and Social Services - Sande, Daniel (Midlands State University, 2017)
The project investigated the decline in Private Employment Agency fees performance in the Ministry of Public Service Labour and Social Services. It also examined the determinants and ways of the effective and efficient ways of collecting licence fees from Private Employment Agencies in Zimbabwe. The objective was to establish an internet base register and analyse the major challenges in the adoption and maintenance of registering Private Employment Agencies on the internet systems in order to come up with ways of mitigating the challenges, ways of increasing client base register in the Ministry of Public Service. Research findings pointed out that the main challenges being faced is the collection of licence fees from Private Employment Agencies on the internet but not registered since they do not have a physical address. Results also indicated corrupt activities that are associated with employment agencies as they perform their duties. Self employment resulted in Private Employment Agencies loosing confidence in providing recruitment services as their core business was affected. It is because of this challenge that Private Employment Agencies have not been renewing their licence certificates on time. Recommendations were that the Ministry should create a website to cater for Private Employment Agencies in Zimbabwe so as to avoid loss of revenue through unregistered Private Employment Agencies on the internet.